Use of conspicuity aids by cyclists and risk of crashes involving other road users: population based case-control study - Miller, Philip; Kendrick, Denise; Coupland, Carol; Coffey, Frank (Elsevier, 2017)
Background: Cycling can improve health and well-being by reducing inactivity. Concern about collision crashes may be a barrier to participation since collision crashes can lead to significant mortality and morbidity. The conspicuity of cyclists may be a contributory factor in some collision crashes. This study investigated whether increased conspicuity aid use (such as reflective or fluorescent clothing) is associated with a reduced risk of collision crashes for cyclists in a UK city.